PERANCANGAN PROTOTIPE UI/UX LAYANAN PEMESANAN BERBASIS MOBILE WEBSITE PADA UMKM LETRA STUDIO MENGGUNAKAN METODE DESIGN THINKING - Brilioneristen; Mia Juliana; Made Nindya Kirana (PT. Hasba Edukasi Mandiri, 2025)
Letra Studio, an MSME photography studio in Jimbaran, faces challenges with its manual reservation system via social media: slow responses, risk of double booking, data management difficulties, and lack of transparency regarding prices and schedules. This process takes over an hour, far exceeding customer expectations of under ten minutes, and results in a System Usability Scale (SUS) score of 45.4 (